Design of an admission order costing model in a private healthcare institution, estado Lara, Venezuela (Gestión y Gerencia, 2026)
This study proposes an admission-order costing model for private healthcare institutions aimed at overcoming the limitations of costing systems based on aggregated cost centers. The model is grounded in absorption costing and a technical departmentalization structure that reorganizes cost accumulation and resource allocation processes. The Admission Order is established as the patient cost accumulation unit, integrating direct medical supplies, professional fees, and indirect costs throughout the healthcare cycle. Methodologically, the research was conducted under a quantitative, descriptive, and field-based approach, with an applied purpose, using a case study strategy to analyze the cost accumulation and allocation structure of a private healthcare institution. The model was implemented through two allocation levels: the first assigned support service costs to healthcare units according to operational causality criteria, and the second allocated costs to patients using time- and usage-based allocation variables. The results show reduced discretion in the allocation of indirect costs through the use of allocation bases consistent with resource consumption associated with healthcare service delivery, thereby improving patient cost traceability. Overall, the model strengthens pricing management and provides a more consistent technical basis for decision-making in private healthcare institutions.
Keywords: hospital costs; admission orders; allocation bases; cost traceability; cost centers